Competition on the University Educational Services Market in Romania and the Protection of Students' Rights and Interests - Gabriel Brătucu; Alexandra Palade (Zamfirache); Anca Madar; Nicoleta Andreea Neacsu; Dana Boşcor; Codruţa Adina Băltescu (Amfiteatru Economic Journal, 2017)
This article aims to quantify the degree in which Romanian students' rights and interests are protected. The authors have conducted a comparative analysis of a descriptive type of five representative university centres in Romania, followed by a quantitative research among students within these centres. Through an exploratory empirical research of a quantitative type, 438 students were interviewed, the results obtained determining the extent in which study programs pursued by respondents live up to student expectations and succeed to satisfy them. Student perception on the services offered in the five university centres considered were also quantified, having identified student intentions regarding their professional path, namely the extent in which there is a continuity between the job and the graduated field of study. Based on the results obtained, the authors recommend to the management of Romanian universities to develop efficient strategies that can afford the protection of students' rights and interests, to permanently identify the needs of the actual and potential customers and to adapt the offer of educational services according to existing requirements on the labor market.
Keywords: A29; I21; I23; M31; P46; 330; protection of students' rights and interests; academic competition; quality of educational services; comparative analysis; quantitative research